The Analysis Study of Stem Cell Show Promising Result for Lymphoedema Treatment : A Comprehensive Systematic Review - Rizki Mudti Nasution; Jefri Bukhori Nasution; Muhammad Arizka Maulana (International Medical Journal Corp. Ltd, 2024)
Background: Lymphedema, a chronic and progressive condition characterized by abnormal lymph fluid accumulation and tissue swelling. This systematic review aims to evaluate the current evidence on stem cell therapy for lymphedema. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2014 to 2024. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: The safety profile of stem cell therapies has been consistently favorable and showed considerable promise in addressing the multifaceted challenges of lymphedema. While clinical and preclinical studies provide encouraging evidence, sustained efforts in research and innovation are essential to establish these therapies as standard treatments for lymphedema.